IAPs cause resistance to TRAIL-dependent apoptosis in follicular thyroid cancer. Issue 3 (March 2018) - Werner, Thomas A; Nolten, Inga; Dizdar, Levent; Riemer, Jasmin C; Schütte, Sina C; Verde, Pablo E; Raba, Katharina; Schott, Matthias; Knoefel, Wolfram T; Krieg, Andreas
Abstract : Follicular thyroid cancer's (FTC) excellent long-term prognosis is mainly dependent on postoperative radioactive iodine (RAI) treatment. However, once the tumour becomes refractory, the 10-year disease-specific survival rate drops below 10%. The aim of our study was to evaluate the prognostic and biological role of the TRAIL system in FTC and to elucidate the influence of small-molecule-mediated antagonisation of inhibitor of apoptosis proteins (IAPs) on TRAIL sensitivity in vitro . Tissue microarrays were constructed from forty-four patients with histologically confirmed FTC. Expression levels of TRAIL and its receptors were correlated with clinicopathological data and overall as well as recurrence-free survival. Non-iodine-retaining FTC cell lines TT2609-bib2 and FTC133 were treated with recombinant human TRAIL alone and in combination with Smac mimetics GDC-0152 or Birinapant. TRAIL-R2/DR5 as well as TRAIL-R3/DcR1 and TRAIL-R4/DcR2 were significantly higher expressed in advanced tumour stages. Both decoy receptors were negatively associated with recurrence-free and overall survival. TRAIL-R4/DcR2 additionally proved to be an independent negative prognostic marker in FTC (HR = 1.446, 95% CI: 1.144–1.826; P < 0.001). In vitro, the co-incubation of Birinapant or GDC-0152 with rh-TRAIL-sensitised FTC cell lines for TRAIL-induced apoptosis, through degradation of cIAP1/2. The TRAIL system plays an important role in FTC tumour biology. Its decoy receptors are associated with poor prognosis as well as earlier recurrence. The specific degradation of cIAP1/2 sensitises FTC cells to TRAIL-induced apoptosis and might highlight a new point of attack in patients with RAI refractory disease.